Combining ferrate(VI) with thiosulfate to oxidize chloramphenicol: Influencing factors and degradation mechanism. Issue 1 (February 2021) - Zhang, Zhuang; Li, Xin; Zhang, Chang; Lu, Sihui; Xi, Yanni; Huang, Yicai; Xue, Zhuangzhuang; Yang, Ting
Graphical abstract: Highlights: The removal rate of CAP increased from 32 % to 69 % by combining Fe(VI) with TS. The Fe(VI)/TS system showed high removal efficiency during the pH ranging 5–9. The SO 4 - / OH and Fe(IV)/Fe(V) active species were responsible for CAP removal. Eight intermediates were found and three possible oxidation pathways were proposed for CAP degradation in Fe(VI)/TS system. Abstract: In this work, combining ferrate (Fe(VI)) with thiosulfate (TS) to degrade chloramphenicol (CAP) was systematically investigated. A series of operational parameters were discussed, including Fe(VI) concentration, TS concentration, pH, molar ratio of TS/Fe(VI), some anions and humic acid. The degradation efficiency of CAP at an initial concentration of 31 μM reached 32 % and 51 % within 120 min and 420 min with single Fe(VI) system, respectively. In comparison, the removal efficiency of CAP reached 69 % under molar ratio of TS/Fe(VI) of 1:8 within 120 min in Fe(VI)/TS system. Additionally, the Fe(VI)/TS system showed higher removal efficiency during the pH ranging 5–9. HCO 3 - had dual effects and PO 4 3 - had obvious inhibitory effect, while Cl -, NO 3 - and HA had no remarkable effects on CAP degradation. The radicals scavenging experiments and electron spin resonance (ESR) experiments demonstrated both sulfate radical and hydroxyl radical were produced in Fe(VI)/TS system, but sulfate radical was the primary active species besides Fe(IV) and Fe(V). Subsequently, eight intermediates were detected by LC–MS/MS and three possible degradation pathways of CAP were proposed. Finally, the toxicity of the by-products was evaluated through the Escherichia coli ( E. coli ) toxicity test.